Analysis of the Influence of Price, Product Accessibility, and Consumer Emotions on Somethinc Skincare User Satisfaction Among the Young Generation of Bali - Adhina Nandatio; Ni Komang Putri Karina Sari (The Journal of Management, Digital Business, and Entrepreneurship, 2024)
This study aims to analyze the effect of price, product accessibility, and consumer emotions on user satisfaction of Somethinc brand skincare among the younger generation in Bali. This study uses a quantitative approach with an associative research type. The independent variables studied are price (X₁), product accessibility (X₂), and consumer emotions (X₃), while the dependent variable is customer satisfaction (Y). The population of the study was the entire younger generation of Somethinc skincare users in Bali, with a non-probability sampling technique through the purposive sampling method. The sample consisted of 62 respondents selected based on certain criteria such as age 17–30 years and product use for at least the last three months. Data were collected using a questionnaire and tested for validity and reliability before being analyzed using multiple linear regression. The results of the study indicate that partially, price and consumer emotions have a positive and significant effect on customer satisfaction. Simultaneously, the three independent variables are also proven to have a significant effect on the level of user satisfaction of Somethinc skincare products. These findings indicate that a marketing strategy that considers competitive price aspects and positive emotional experiences will have a significant impact on increasing the satisfaction and loyalty of young consumers. The practical implications of these results provide a basis for companies to develop more focused and customer experience-based marketing strategies, especially in the dynamic and competitive skincare market.